Replacing animal models : a practical guide to creating and using culture-based biomimetic alternatives - Davies, Jamie A. (Wiley-Blackwell, 2012)
"The book is neither political nor polemical : it is technical, illustrating by example how alternatives can be developed and used and providing useful advice on developing others. After looking at the reasons for and potential benefits of alternatives to animal experiments, the book covers a range of methods and examples emphasising the design considerations that went into each system. The chapters also include 'case studies' that illustrate the ways in which culture models can be used to answer a range of important biological questions of direct relevance to human development, physiology, disease and healing."-- Provided by publisher